The Application of a New Microbial Biosurfactant to Remove Residual Oil from Electric Power Plant and to Inhibit Metal Corrosion in a Salty Environment - Alexandre Augusto P. Selva Filho; Yslla Emanuelly S. Faccioli; Attilio Converti; Alessandro Alberto Casazza; Rita de Cássia F. Soares da Silva; Leonie A. Sarubbo (Energies)
Human development has led to increased production of oil and gas, mainly as energy sources, which, however, are responsible for contamination and metal corrosion in industrial, marine, and terrestrial environments. Lubricating oil, in particular, is widely used in generators and industrial machines in the electric sector and is responsible for contamination not only in industrial environments but also in many terrestrial and aquatic ecosystems. In this context, this study aimed to apply the Starmerella bombicola ATCC 222214 biosurfactant to inhibit metal corrosion in seawater and in an Accelerated Corrosion Chamber (ACC). For this purpose, its toxicity against the microcrustacean Artemia salina, its dispersion capacity, and its ability to promote oil biodegradation in a saline environment were investigated. The biosurfactant, when applied at twice its Critical Micellar Concentration (CMC), caused low mortality (30.0%) of microcrustaceans in a saline environment, and, in its crude form, the biosurfactant ensured the dispersion of no less than 77.56% of residual engine oil in seawater. Oil biodegradation by autochthonous microorganisms reached 94.39% in the presence of the biosurfactant in seawater. Furthermore, the biosurfactant, when used at twice its CMC, acted satisfactorily as a corrosion inhibitor by reducing the mass loss of galvanized iron specimens (plates) in seawater in a static system to only 0.36%. On the other hand, when the biosurfactant was added at the CMC as an atmospheric corrosion inhibitor, the reduction in mass loss of carbon steel plates treated in the ACC was 17.38% compared to the control containing only a biodegradable matrix based on vegetable resin. When the biosurfactant was incorporated into different paints applied to galvanized iron plates placed in contact with the salt spray produced in the ACC, the best result was obtained using the biomolecule at a concentration of 3% in the satin paint, ensuring a plate mass loss (29.236 g/m2) that was almost half that obtained without surfactant (52.967 g/m2). The study indicated the use of yeast biosurfactant as a sustainable alternative in combating the contamination of marine environments and metal corrosion, with the aim of preserving the environment and improving the quality of life in aquatic and terrestrial ecosystems.